(untitled) (Medico Legal Update, 2021)
The subject of mood disorders and death anxiety in the elderly is considered one of the topics that have been addressed only slightly and in limited ways in relation to general trends and psychological research in other subjects in terms of quality and quantity. As well as if there is a statistically significant effect of sex variables, the sample of the study consisted of all the elderly who were able to respond to the researcher, which amounted to (110) elderly people, including (65) males and (45) females. We collected demographic information about the elderly, as well as translating the mood disorders scale, as well as the arithmetic averages, percentages, deviations and the Pearson correlation coefficient were used. To reach the results of the study, a number of results were reached. The suffering of elderly people living in nursing homes in the capital, Baghdad, from a high level of mood disorders. The suffering of the elderly residing in the nursing homes of the capital, Baghdad, from a moderate feeling in the level of death anxiety. There are statistically significant differences at the level of (0.05) between the elderly on the measures of mood disorders and death anxiety that are related to the gender variable and return to the benefit of females. There is no statistically significant relationship between mood disorders and death anxiety among the study sample.